Peningkatan Kemampuan Berpikir Kritis Siswa Kelas IV SD dengan Menggunakan Model PBL Berbantu Media Papan Madu - Nanda Ragil Setyawan; Savitri Wanabuliandari; Diana Ermawati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to determine the application of the honey board-assisted PBL learning model to improve critical thinking skills in mathematics of fourth grade students of Medini 2 Public Elementary School. This class research was conducted in fifth grade of Boloagung 02 Public Elementary School with 20 students and teachers as test subjects, who lasted for 2 cycles. Each cycle consists of two meetings. The dependent variable is students' critical thinking skills and the independent variable is the Problem Based Learning model assisted by Honey Boards. Data collection methods used include interviews, observation, tests and documentation with quantitative and qualitative analysis techniques. The results of the study showed that students' critical thinking skills after applying the Problem Based Learning model assisted by the Honey Board in Cycle I obtained a score of 76.67 with a percentage of 71%, and student completeness reached 65%. The increase in the results of critical thinking skills in cycle II was 78.67 with a percentage of 79% and the percentage of students' completeness was 90%. So, the application of the PBL learning model assisted by the honey board can improve the mathematical critical thinking skills of fourth grade students at SD Negeri Medini 2.